A Simple, Sensitive Spectrophotometric Assay for Extrinsic (Tissue-Type) Plasminogen Activator Applicable to Measurements in Plasma - Verheijen, J H; Mullaart, E; Chang, G T G; Kluft, C; Wijngaards, G (Thrombosis and Haemostasis, 1982)
An indirect spectrophotometric assay for extrinsic plasminogen activator has been devised, which is based on the parabolic assay of Drapier et al. (5). The system contains activator, plasminogen, the synthetic plasmin substrate H-D-Val-Leu-Lys-pNA (S-2251, Kabi) and a mixture of soluble fibrinogen fragments prepared by treatment of fibrinogen with cyanogen bromide. The addition of these fibrinogen fragments considerably enhances the sensitivity and specificity of the method owing to specific stimulation of the plasminogen activation by extrinsic plasminogen activator.The assay conditions were optimized and the application for extrinsic plasminogen activator measurements in plasma euglobulin fractions is demonstrated.
Keywords: Plasminogen activator assay; Sensitive; Spectrophotometric fibrin fragment; Synthetic substrate